1997
DOI: 10.1016/s0167-4889(96)00171-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenic ion transport in the mouse endometrium: functional aspects of the cultured epithelium

Abstract: A primary culture of mouse endometrial epithelium grown on permeable supports was established and the electrogenic ion transport across the endometrial epithelium was studied using the short-circuit current (I(SC)) technique. Enzymatically isolated mouse endometrial cells were immunostained with epithelial cells markers, cytokeratins, indicating an epithelial origin of the culture. Mouse endometrial epithelial cells grown on Millipore filters formed polarized monolayers with junctional complexes as revealed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 15 publications
4
22
0
Order By: Relevance
“…Previous studies have shown that cultured endometrial epithelia exhibit a basal Isc which is predominantly amiloride-sensitive, indicative of Na ϩ absorption which could be switched to predominant CFTRmediated anion secretion upon stimulation (10,16,17). In the present study, variations in basal Isc were observed for different batches of cultured endometrial epithelia.…”
Section: Amiloride Sensitivity Of the Basal Isc And The Forskolin-indsupporting
confidence: 52%
See 1 more Smart Citation
“…Previous studies have shown that cultured endometrial epithelia exhibit a basal Isc which is predominantly amiloride-sensitive, indicative of Na ϩ absorption which could be switched to predominant CFTRmediated anion secretion upon stimulation (10,16,17). In the present study, variations in basal Isc were observed for different batches of cultured endometrial epithelia.…”
Section: Amiloride Sensitivity Of the Basal Isc And The Forskolin-indsupporting
confidence: 52%
“…Endometrial epithelial cells were enzymatically isolated from the mouse uterus according to the method described by McCormack and Glasser (9) with slight modifications (10). The isolated endometrial cells were plated on nitrocellulose Millipore filters (0.45 cm 2 ) without or with Matrigel coating.…”
Section: Methodsmentioning
confidence: 99%
“…Endometrial epithelial cells were isolated enzymatically from the mouse uterus according to [15] with slight modifications [5]. Uteri were obtained from 3.5-to 4-week-old immature ICR mice to avoid the complication of the oestrous cycle.…”
Section: Cell Culturementioning
confidence: 99%
“…Recent studies on primary cultures of mouse endometrial epithelium have demonstrated predominantly Na + absorption under basal conditions but mostly anion secretion upon stimulation [4,5,6,9]. Cultured endometrial epithelium responds to adrenaline, noradrenaline, prostaglandin E 2 (PGE 2 ) or forskolin with an increase in the short-circuit current (I sc ) that can be attributed predominantly to Cl -and HCO 3 -secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Increased ENaC activity by culture conditions. Previous studies have shown that cultured endometrial epithelia exhibit a basal I SC that can be effectively blocked by amiloride, indicative of predominant Na ϩ absorption [10,13]. We recently found that the ENaC activity of endometrial cultures could be affected by coating the permeable support with Matrigel [14], which resembles the extracellular matrix facilitating rapid epithelial reconstitution and differentiation [15,16].…”
Section: Introductionmentioning
confidence: 99%